2020
DOI: 10.1128/jvi.02038-19
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells and STAT1 Signaling Are Essential Codeterminants in Protection from Polyomavirus Encephalopathy

Abstract: JC polyomavirus (JCPyV), a human-specific virus, causes the aggressive brain-demyelinating disease progressive multifocal leukoencephalopathy (PML) in individuals with depressed immune status. The increasing incidence of PML in patients receiving immunotherapeutic and chemotherapeutic agents creates a pressing clinical need to define biomarkers to stratify PML risk and develop anti-JCPyV interventions. Mouse polyomavirus (MuPyV) CNS infection causes encephalopathology and may provide insight into JCPyV-PML pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Because virus-specific CD8 T EFF also express high-affinity TCRs, we suggested that these cells were the progeny of high-affinity effectors recruited to the brain during the acute stage of infection ( 68 ). Indeed, we observed that there is a window of opportunity for immune cells, and possibly virus, to breach a blood-brain barrier rendered permeable during acute MuPyV encephalitis ( 69 ). A plausible possibility is that high-affinity TCRs enable CD8 bT RM to detect low levels of viral antigen during persistent infection ( 68 ).…”
Section: Tcr Signal Strength As a Driver Of T Rm Fmentioning
confidence: 99%
“…Because virus-specific CD8 T EFF also express high-affinity TCRs, we suggested that these cells were the progeny of high-affinity effectors recruited to the brain during the acute stage of infection ( 68 ). Indeed, we observed that there is a window of opportunity for immune cells, and possibly virus, to breach a blood-brain barrier rendered permeable during acute MuPyV encephalitis ( 69 ). A plausible possibility is that high-affinity TCRs enable CD8 bT RM to detect low levels of viral antigen during persistent infection ( 68 ).…”
Section: Tcr Signal Strength As a Driver Of T Rm Fmentioning
confidence: 99%
“…In support of a choroid plexus-mediated route, JCPyV infects primary choroid plexus epithelial cells, and JCPyV-infected choroid plexi are found in PML brains (Corbridge et al, 2019;O'Hara et al, 2020O'Hara et al, , 2018. Both A2 and A2.V296F viruses productively infect the ependyma, and we reported ependymal infection by MuPyV under conditions of immune suppression (Mockus et al, 2020). Infection of the choroid plexus and ependyma may serve as a viral staging area for JCPyV invasion of the brain parenchyma, providing a foothold for viral dissemination in the CNS parenchyma.…”
Section: Discussionmentioning
confidence: 52%
“…Immunocompetent mice infected with MuPyV do not develop productive kidney infection when detected by immunofluorescence or immunohistochemistry (Drake and Lukacher, 1998). Stat1 -/mice depleted of CD8 + T cells develop severe systemic MuPyV infection (Mockus et al, 2020). We compared A2 and A2.V296F kidney infection in CD8 + T cell-depleted Stat1 -/mice by staining kidney sections at day 7 pi for VP1.…”
Section: V296f Vp1 Mutation Retains Mupyv Tropism For Brain But Not Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocompetent mice infected with MuPyV do not develop productive kidney infection when detected by immunofluorescence or immunohistochemistry (Drake and Lukacher, 1998). STAT1 -/mice depleted of CD8 + T cells develop severe systemic MuPyV infection (Mockus et al, 2020). We compared A2 and A2.V296F kidney infection in CD8 + T cell-depleted STAT1 -/mice by staining kidney sections at day 7 pi for VP1 and CD13, which marks proximal tubules in the kidney cortex (Guder and Ross, 1984;Van der Hauwaert et al, 2013).…”
Section: V296f Vp1 Mutation Retains Mupyv Tropism For Brain But Not Kmentioning
confidence: 99%